REVIEW: ADVERSE DRUG REACTIONS AND PHARMACOKINETIC CHARACTERISTICS OF LINEZOLID AS A THERAPY FOR DRUG RESISTANT TUBERCULOSIS - Retnaningsih, Ririn; Susilo, Rinto; Sundhani, Elza (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Introduction: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that remains a global health challenge. One of the main problems in TB treatment is the emergence of drug resistance, such as in multidrug-resistant tuberculosis (MDR-TB). Linezolid is a class of oxazolidinones used as second-line therapy in the treatment of drug-resistant TB. However, its use is not free from serious adverse drug reactions such as peripheral neuropathy, myelosuppression, and lactic acidosis. Therefore, understanding the pharmacokinetic profile and adverse drug reactions of linezolid is important to increase the effectiveness of therapy and minimize the risk of toxicity. Objective: This study aimed to evaluate the adverse drug reactions caused by linezolid and analyze its pharmacokinetic characteristics in the treatment of drug-resistant tuberculosis (TB). Methods: This article is a literature review that collects data from national and international scientific sources over the past 10 years (2015-2025), including the addition of comparative studies or meta-analyses, as well as inclusion criteria, such as articles that discuss the pharmacokinetics, adverse drug reactions, and use of linezolid in drug-resistant tuberculosis therapy, either in clinical trials, observational studies, or relevant therapeutic guidelines. Results: Based on the results of various studies, linezolid has an oral bioavailability approaching 100%, which allows oral and intravenous administration with almost equivalent doses. Its pharmacokinetic profile shows an elimination half-life of approximately 5-7 hours, with primary metabolism via nonenzymatic oxidation in the liver and excretion in the urine as inactive metabolites. These characteristics make linezolid a flexible option for drug-resistant tuberculosis therapy..